Mujer y espacio sagrado: haciendo visibles a las mujeres en los lugares de culto de época ibérica - Prados Torreira, Lourdes (Complutum, 2007)
Woman and sacred space. Making women visible in sacred sanctuaries in Iberian Culture. From the gender archaeology and religious and ritual focus during the Iberian Culture (6th-1st Centuries BC), I present an approach to the woman’s role and its meaning in the different ritual ceremonies. I propose several studies cases on Iberian sanctuaries where it would be possible to analyze the woman’s role.